Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1212/wnl.0000000000001184
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency stimulation of STN-DBS reduces aspiration and freezing of gait in patients with PD

Abstract: Objectives: To study whether 60-Hz stimulation, compared with routine 130 Hz, improves swallowing function and freezing of gait (FOG) in patients with Parkinson disease (PD) who undergo bilateral subthalamic nucleus (STN) deep brain stimulation (DBS). Methods:We studied 7 patients with PD who experienced FOG that persisted despite routine 130-Hz stimulation and dopaminergic medication. Each patient received 3 modified barium swallow (MBS) studies in a single day under 3 DBS conditions in the medication-on stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 26 publications
(36 reference statements)
3
167
0
2
Order By: Relevance
“…In particular, short pulse widths decrease the activation of surrounding fibers as a result of specific axon properties such as chronaxie. Recently, an increasing number of reports have explored the use of low-frequency stimulation (60-80 Hz) to improve axial symptoms including freezing of gait, postural control, dysarthria, swallowing function and also bradykinesia [50,[52][53][54][55]. However, these reports only addressed the short-term effects, and the initial promising results were limited either by the transient clinical benefits or worsening of appendicular symptoms [52,56].…”
Section: Stn Imaging and Target Selectionmentioning
confidence: 99%
“…In particular, short pulse widths decrease the activation of surrounding fibers as a result of specific axon properties such as chronaxie. Recently, an increasing number of reports have explored the use of low-frequency stimulation (60-80 Hz) to improve axial symptoms including freezing of gait, postural control, dysarthria, swallowing function and also bradykinesia [50,[52][53][54][55]. However, these reports only addressed the short-term effects, and the initial promising results were limited either by the transient clinical benefits or worsening of appendicular symptoms [52,56].…”
Section: Stn Imaging and Target Selectionmentioning
confidence: 99%
“…Recently, we found that 60 Hz stimulation improved swallowing dysfunction, along with FOG and overall axial and motor symptoms, in PD patients with FOG at HFS and medication on state 18. This is important, as dysphagia is commonly present in PD,19 and often refractory to pharmacological management,20 21 with high risk of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 94%
“…This is important, as dysphagia is commonly present in PD,19 and often refractory to pharmacological management,20 21 with high risk of morbidity and mortality. However, it remains unknown whether there is a long-term benefit on swallowing function beyond the 6 weeks studied,18 especially considering the potential disease progression and potential carryover effect associated with the order of DBS assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found that using 60 Hz instead of 130 Hz subthalamic stimulation significantly reduced number of FOG episodes [76,77]. Furthermore, improvements in dysarthria and aerodynamic speech parameters with 60 Hz compared to 130 Hz subthalamic stimulation have been reported [78].…”
Section: Dbs Programmingmentioning
confidence: 99%
“…Furthermore, improvements in dysarthria and aerodynamic speech parameters with 60 Hz compared to 130 Hz subthalamic stimulation have been reported [78]. Importantly, the use of low-frequency stimulation is also associated with a reduced aspiration tendency, as demonstrated by barium swallow studies, along with a reduction of perceived swallowing difficulty [76]. Low-frequency stimulation might even help to overcome STN DBS-induced verbal fluency impairment [79].…”
Section: Dbs Programmingmentioning
confidence: 99%